Pengaruh Strategi Pembelajaran Index Card Match Dalam Meningkatkan Hasil Belajar Akidah Akhlak Peserta Didik Kelas V Madrasah Ibtidaiyah Muhammadiyah 01 Pondok Modern Paciran - Ratna Dwi Aprilia Himmatul Husniyah (STIT Muhammadiyah Paciran, 2021)
Lack of application of innovative learning strategies in Aqidah Akhlak learning makes learners passive and less interested in learning which results in low learning outcomes. Learning strategy is a way that can be done by educators so that the learning process runs effectively because with the selection of the right learning strategy greatly affects the high learning outcomes of learners. To overcome these problems, researchers apply index card match learning strategies with the aim to improve the learning outcomes of Aqidah Akhlak learners of class V MI Muhammadiyah 01 Pondok Modern Paciran lesson year 2020/2021. This research uses this type of quantitative research. The population and sample of this study were class V learners as many as 39. Sampling technique uses saturated samples. The research design used is One group pretest-posttest design. Data collection is done using tests. After the data test is collected then the data processing is carried out with statistical analysis using the t test signifikasni. Based on the results of the study obtained the average prettest learning results = 49,743 while the average posttest learning results = 76,282.As well as significance obtained thitung = 6.03 and ttabel = 2,026 (thitung>ttabel). That is, H0 is rejected and H1 is accepted. This shows that there is an influence of Index Card Match learning strategy in improving the learning outcomes of Aqidah Akhlak class V MI Muhammadiyah 01 Pondok Modern Paciran lesson year 2020/2021.